Key performance indicators in boxing: a 3D markerless protocol based on action cameras - Pagnon, D.; Domalain, M.; Robert, T.; Lahkar, B. K.; Moussa, I.; Sauliere, G.; Goyallon, T.; Reveret, L. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Marker-based kinematics is hardly compatible with sports movement analysis, especially because it hinders natural movement. Hence, deep-learning based markerless solutions are being developed, such as Pose2Sim [1]. Sports in competition may also be subject to setup constraints, preventing the use of heavy equipment and installation. The use of lightweight action cameras, with post-calibration and post-synchronization, can be pertinent in this context. This study aimed at investigating the accuracy of the Pose2Sim pipeline in such suboptimal conditions. We assessed the measures of key performance indicators in boxing, which involves swift and 3-dimensional full-body movements.